2019
DOI: 10.1177/0306624x19834408
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Comparison of Canadian and Korean Sexual Homicide

Abstract: Sexual homicide is a crime of rare occurrence. However, crime severity surveys ranked this form of sexual violence as the second most serious crime. Despite an increase in recent years in the publication of empirical studies on sexual homicide, most of these studies originate from Western countries. Therefore, to our knowledge, no studies to date have tested whether the country where sexual homicides are committed influences the way these crimes are executed by the offenders. The current study attempts to shed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 26 publications
5
26
0
Order By: Relevance
“…Therefore, it is possible that the availability of space for Canadian SHOs influenced their decision to dump the victim's body outdoor, whereas for French SHOs, maybe this alternative is not as convenient. Sea et al (2019) have noticed a similar pattern with Korean SHOs who also were more likely to dismember the victim's body.…”
Section: Shsupporting
confidence: 54%
See 3 more Smart Citations
“…Therefore, it is possible that the availability of space for Canadian SHOs influenced their decision to dump the victim's body outdoor, whereas for French SHOs, maybe this alternative is not as convenient. Sea et al (2019) have noticed a similar pattern with Korean SHOs who also were more likely to dismember the victim's body.…”
Section: Shsupporting
confidence: 54%
“…At the time of offence, French and Canadian victims were 31 and 27.9 years old, respectively . Whereas Korean victims were much older than Canadians with an average age of 43.53 years (Sea et al, 2019). In the study by , only a few significant differences in victim characteristics were observed.…”
Section: International Comparison Of Sexual Homicides Victimsmentioning
confidence: 55%
See 2 more Smart Citations
“…While there were some bivariate differences, for instance in regards to the use of restraints and the destruction of evidence, the two samples overall displayed stark similarities. Similarly, Sea, Beauregard, and Martineau (2019) compared Canadian and North Korean sexual homicide, demonstrating an overall similarity between countries, despite bivariate differences such as forensic awareness, type of weapon used and age of offender. However, no multivariate or typological analyses were undertaken in either study, highlighting the need for more sophisticated methodology in comparative research.…”
Section: International Comparative Researchmentioning
confidence: 98%